JATISABA (2015) AND ELEVEN MINUTES (2003) FROM A PSYCHOANALYTIC FEMINIST PERSPECTIVE: A COMPARATIVE STUDY - Rizki Eka Putri Alda (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
This study analyzes Jatisaba, a novel by Ramayda Akmal and Eleven Minutes, a novel by Paulo Coelho, within a comparative literature framework. It aims to compare the transformation of the main female characters and their struggle to survive in both novels. By means of a descriptive qualitative method, the research was conducted from a psychoanalytic feminist perspective. This perspective believes that women are not born inferior, but some factors in her life have been placing them in an inferior position to men. The study resulted in the following findings. First, the main characters of both novels, Mae and Maria, underwent a psychological transformation throughout their life journeys of surviving human trafficking, sexual harassment and prostitution and navigating their love lives Both of them were brought up by a mother with a strong character that could protect them from castration and gender inferiority as a woman. Second, Mae and Maria’s struggle to survive became the cause of their resistance against patriarchal values with the power of their femininity. Third, the difference between the endings of the two novels reflects the different social and cultural values in the respective stories that greatly influence the female characters’ lives. Penelitian ini bertujuan untuk menganalisa novel Jatisaba karya Ramayda Akmal dari Indonesia dan Eleven Minutes karya Paulo Coelho dari Brazil menggunakan pendekatan sastra banding. Penelitian ini mengungkap transformasi karakter dari tokoh utama perempuan dalam kedua novel dan cara mereka bertahan hidup dalam dunia yang didominasi oleh budaya patriarki. Penelitian ini menggunakan metode deskriptif kualitatif dan perspektif feminis psikoanalisis. Perspektif ini berpandangan bahwa perempuan tidak dilahirkan sebagai makhluk inferior, tetapi ada beberapa faktor dalam hidup mereka yang dapat menyebabkan mereka berada pada posisi inferior. Hasil penelitian mengungkap tiga hal berikut ini. Pertama, transformasi psikologis dari tokoh utama perempuan dalam kedua novel, Mae dan Maria, merupakan hasil dari perjalanan hidup mereka melalui pengalaman-pengalaman seperti perdagangan manusia, kekerasan seksual dan prostitusi serta kehidupan percintaan. Keduanya dibesarkan oleh sosok ibu yang tangguh yang melindungi mereka dari kastrasi dan inferioritas sebagai perempuan. Kedua, perjuangan untuk bertahan hidup yang ditunjukkan Maria dan Mae menggambarkan perlawanan terhadap nilai-nilai patriarki menggunakan femininitas mereka Ketiga, pengaruh faktor-faktor sosial dan budaya terhadap pembentukan karakter kedua tokoh utama tersebut tercermin dalam akhir cerita yang berbeda antara novel Jatisaba dan Eleven Minutes.